Semisynthesis of Derivatives of Oleanolic Acid from Syzygium aromaticum and Their Antinociceptive and Anti-Inflammatory Properties - Sibusiso Rali; Opeoluwa O. Oyedeji; Olukayode O. Aremu; Adebola O. Oyedeji; Benedicta N. Nkeh-Chungag (Mediators of Inflammation)
Oleanolic acid is a pentacyclic triterpenoid compound widely found in plants and well known for its medicinal properties. Oleanolic acid (OA) was isolated from the ethyl acetate extract of Syzygium aromaticum flower buds. Semisynthesis afforded both acetate and ester derivatives. The derived compounds were monitored with thin layer chromatography and confirmed with nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), Fourier infrared (FT-IR) spectroscopy, and melting point (Mp). All these compounds were evaluated for their analgesic and anti-inflammatory properties at a dose of 40 mg/kg. Significant analgesic and anti-inflammatory effects were noted for all OA-derived compounds. In the formalin-induced pain test, the derivatives showed better analgesic effects compared to their precursor, whereas, in the tale flick test, oleanolic acid proved to be superior in analgesic effects compared to all its derivatives with the exception of the acetyl derivative. Acute inflammatory tests showed that acetyl derivatives possessed better anti-inflammatory activity compared to the other compounds. In conclusion, semisynthesis of oleanolic acid yielded several derivatives with improved solubility and enhanced analgesic and anti-inflammatory properties.